2013
DOI: 10.1021/pr3010452
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling to Identify Potential Serum Biomarkers for Gastric Ulceration Induced by Nonsteroid Anti-Inflammatory Drugs

Abstract: Nonsteroid anti-inflammatory drugs (NSAIDs) are among the most frequently prescribed drugs currently available. The most frequently reported serious side effects associated with NSAIDs are gastric mucosal ulceration and gastric hemorrhage. Presently, these side effects are only detectable by endoscopy, however, and no biomarkers have yet been identified. The ability to identify serum biomarkers would likely improve the safety of NSAID use. In this study we performed capillary electrophoresis-mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 26 publications
(38 reference statements)
2
34
0
Order By: Relevance
“…We previously reported five biomarker candidates in serum that predict gastric injury induced by NSAIDs in rats 5. We also reported that the decrease in hydroxyproline in stomach induced by aspirin recovered to the control level on co-administration with omeprazole and famotidine.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We previously reported five biomarker candidates in serum that predict gastric injury induced by NSAIDs in rats 5. We also reported that the decrease in hydroxyproline in stomach induced by aspirin recovered to the control level on co-administration with omeprazole and famotidine.…”
Section: Introductionmentioning
confidence: 88%
“…System control and data acquisition were done using the Agilent G2201AA ChemStation software for CE and Analyst QS software for TOF–MS. Annotation tables were generated by the same method used in our previous study 5,6…”
Section: Methodsmentioning
confidence: 99%
“…They have serious side effects of gastric mucosal ulceration and gastric hemorrhage. Takeuchi et al applied a shotgun approach based on CE-TOFMS profiles of endogenous metabolites to identify new biomarkers of NSAID-induced gastric injury in rat stomach tissue [59]. The levels of citric acid, cis-aconitic acid, succinic acid, 3-hydroxybutanoic acid, o-acetyl carnitine, proline, and hydroxyproline were decreased in the NSAID stomach tissue compared with the healthy tissue.…”
Section: Tissuementioning
confidence: 99%
“…Effective sample preparation with minimal sample loss is particularly important in the study of the metabolomics of neurodegenerative disease where CSF samples may be limited to only a few milliliters. To address these challenges, methods such as solid-phase microextraction have been developed (Cudjoe, Bojko, de Lannoy, Saldivia, & Pawliszyn, 2013) as well as ion mobility spectrometry (Castro-Perez et al, 2011;Sowell et al, 2004;Zinnel, Pai, & Russell, 2012) and capillary electrophoresis-mass spectrometry (Nevedomskaya et al, 2010;Takeuchi et al, 2013).…”
Section: Metabolomics Platforms For Biomarker Discoverymentioning
confidence: 99%